(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study investigates several factors related to surgical time, postoperative hospital stay, and postoperative complications of robotic-assisted laparoscopic nephrectomy for non-functioning kidneys due to certain benign pathologies. Subjects and methods: We conducted a descriptive study with retrospective and prospective components on 73 patients treated at Thanh Hoa provincial General Hospital from January 2022 to June 2025. Univariable analyses were followed by generalized linear models for operative time and postoperative hospital stay, and multivariable logistic regression for postoperative complications. Results: Mean operative time was 71.6 minutes, mean postoperative hospital stay was 8.2 days, and the postoperative complication rate was 15.1%. Absence of previous renal disease treatment reduced operative time by 14.4% compared with a positive treatment history (p = 0.035). Each additional day before drain removal increased postoperative hospital stay by 3.2% (p = 0.001), whereas absence of postoperative complications reduced hospital stay by 36.4% (p < 0.001). Intraoperative blood transfusion was independently associated with a higher risk of postoperative complications (OR = 15.353; 95% CI: 1.748-134.877; p = 0.014). Conclusions: Patients with no prior medical history, including internal medical conditions and renal disease, had a 14.4% shorter operative time than those with a history of comorbidities. Each 1-day increase in drainage removal time was associated with a 3.2% increase in postoperative length of hospital stay. The absence of postoperative complications reduced the postoperative hospital stay by 36.4%. The indication for blood transfusion was associated with an approximately 15-fold higher risk of complications compared with no transfusion.